Power generation technologies - Breeze, Paul A. (2014)
The new edition of Power Generation Technologies is a concise and readable guide that provides an introduction to the full spectrum of currently available power generation options, from traditional fossil fuels and the better established alternatives such as wind and solar power, to emerging renewables such as biomass and geothermal energy. Technology solutions such as combined heat and power and distributed generation are also explored. However, this book is more than just an account of the technologies - for each method the author explores the economic and environmental costs and risk factors. Each technology is covered using the same basic criteria so that comparisons between technologies can be made more easily. Those involved in planning and delivering energy - including engineers, managers and policy makers - will find in this book a guide through the minefield of maintaining a reliable power supply, meeting targets on greenhouse gas emissions, and addressing economic and social objectives. Provides a unique comparison of a wide range of power generation technologies from oil, coal, nuclear and natural gas, to geothermal, wind, solar, and bioenergyHundreds of diagrams demystify how each technology functions in practiceEvaluates the economic and environmental viability of each power generation system covered NEW TO THIS EDITION: New chapters covering fast-advancing renewable and alternative power sources such as municipal waste and concentrating solar plantsFresh focus the evolution of traditional technologies such as natural gas and "clean coal"Expanded coverage of distributed power generation and CHP (combined heat and power) technologies.
Includes index.
.
Keywords: Electric power production; Electric power production; Electronic books